PREDICTION OF PIT LAKE WATER QUALITY IN COAL MINING (CASE STUDY IN PIT ABC PT XYZ) - RAIN PRATAMA (NIM : 22115021), GINDANG
Mine Acid Water is formed due to three main factors, namely sulfide, oxygen and water minerals. At the end of the mining period, an open coal mine will form a pit lake whose water quality is influenced by the quality of the leach water for each lithology of the pit wall rock. In the research area, PT XYZ, pit wall rock lithology consists of 30% of potentially acidic rocks and 70% of non-acidic rocks with sump water quality have a low pH. The prediction of water quality in pit lake was done by making three scenarios of mixing of leachate water on each pit wall lithology using PHREEQC software with geochemical characteristics data, leach water quality, and mineral content in the rock. The results of the static test of all samples were categorized as PAF. Whereas from the kinetic test results, the sample pH value is sample S1 is 6.05, the sample S2 is 6.62, the sample S3 is 2.36 and the sample S4 is 6.28, indicating that the acidity marker with a low pH value is a sample of S3. The pH ratio of the kinetic test and the pH of the simulation using PHREEQC software with the inverse modeling method that is, the S1 sample has a pH of 6.05 in kinetic test and 6.59 in the simulation. The S2 sample had a pH of 6.62 kinetic test and 6.37 in the simulation. S3 samples have a pH of 2.36 in the kinetic test and in the simulation. S4 samples have a kinetic test pH of 6.28 and 6.21 in the simulation. Reacting minerals include pyrite, quartz, hematite, camontmorillonite, kaolinite, calcite, and oxygen. Pit lake is fully charged in the 36th year with a total volume of water of 24,000,000 m3 and will fill 32 years if in the existing water condition 5%. The three mixing scenarios used in this study are optimistic scenario with S1 sample representing pit wall lithology, conservative scenario with S3 sample representing pit wall lithology, and proportional scenario with all samples representing pit wall lithology. The optimistic scenario shows an increase in the pH value from 6.75 to 6.8 in the 36th year. The conservative scenario shows an increase in the pH value from 2.85 to 3.13 in the 36th year. Whereas in the proportional scenario where all rock samples involved have an increase in pH values from 3.24 to 3.42 in the 36th year. If the Pit Lake has been filled with water as much as 5% of the total volume of water with the actual water quality of the sump, the optimistic scenario shows an increase in the pH value from 2.86 to 5.81 in the 32nd year. The conservative scenario shows a decrease in the pH value from 2.86 to 2.76 in the 32nd year. While the proportional scenario has an increase in the pH value from 2.86 to 3.05 in the 32nd year.